Implementation of Pancasila Values in Preventing and Handling Sexual Violence in Higher Education - Amallia, Nesty; Nissa, Haura Chairun; Marselina, Dina; Shahzada, Rafi; Antoni, Herli (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Sexual violence is a pressing social issue in Indonesia, including within higher education institutions. This study aims to analyze the implementation of Pancasila values in preventing and addressing sexual violence in universities, identify challenges faced, and develop strategic recommendations based on Pancasila principles. The study employs a qualitative approach using literature review and thematic analysis on policies, educational programs, and societal culture. Findings indicate that policies such as Permendikbudristek No. 30 of 2021 and the Sexual Violence Law (UU TPKS) reflect the application of the second and fifth Pancasila principles in providing protection for victims and preventing sexual violence. Character education programs based on Pancasila values in several universities show significant potential in shaping students' moral awareness, although their implementation is uneven. Major challenges include patriarchal norms, social stigma against victims, and limited funding and human resources. The study recommends strengthening policies, equalizing character education, and public awareness campaigns based on Pancasila values to create a safe and dignified educational environment. The implications of this study can serve as a foundation for future policy and strategic program development.